PENGAWASAN PENDIDIKAN FORMAL UNTUK MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA PERBATASAN DI KABUPATEN SANGGAU - Wibowo, Arif (Legal Standing : Jurnal Ilmu Hukum, 2019)
This research is about the function of the Regional Head of Sanggau District in conducting supervision in the field of education in Sanggau District, to find out the juridical constraints that have caused the quality of the education sector to not increase according to educational standards and to know the legal measures that must be implemented so that the Supervision function can improve the quality of the education sector. This study is a normative juridical legal research, namely research conduct a search of legal norms contained in the regulations applicable legislation regarding Education. Data that has been collected both from the results of library research and from the field research are then analyzed qualitatively descriptive.The research results show that the implementation of the regent's function as the head of the district Sanggau in providing services in the field of education in order to improve the quality of education in the implementation of the function of conducting supervision in the field of education